Accuracy of Approximation - Al-Doori, Younis A.; Ghareeb, Najmaddin H. (Sulaimani Journal for Pure and Applied Sciences, 2004)
It is introCuced, here, and defined a rneasure of accuracy of approxirnation, of a function by another. Few examples are presented to illustrate its usage.
Keywords: limit; convergence; accuracy; approximation; series; factorials; Sterling